Allocation concealment: a methodological review. Issue 4 (7th May 2013) - Clark, Laura; Schmidt, Ulrike; Tharmanathan, Puvan; Adamson, Joy; Hewitt, Catherine; Torgerson, David
Abstract Rationale, aims and objectives The accurate reporting of the trial methodology and results is essential for accurate judgement on the quality of the research. This review aims to assess the impact of the adequacy of allocation concealment on treatment effect estimates. Methods A search was performed in MEDLINE (via the Ovid platform) to identify all randomized controlled trials (RCTs) indexed in January 2011 within its set of 'core clinical journals'. Meta‐regression was undertaken on a subset of two arm trials to quantify the association between adequacy of allocation concealment and effect size. Results Adequate allocation concealment methods were used in 27% (n = 23) of included trials. There was insufficient information given in 68% (n = 58) of trials to make a judgement on allocation concealment. Meta‐regression showed that there was a trend, not statistically significant, towards a smaller effect size between adequacy of allocation concealment and effect sizes. Conclusion This review highlighted that research needs to be reported to a higher standard and there are many trials reporting poor methods of allocation concealment within the small sample of trials included in this review.